Magnetoelectricity at room temperature in the LaFeO3/BiFeO3 heterostructures - Ranieri, M. G. [UNESP]; Amoresi, R. A.C. [UNESP]; Ramirez, M. A. [UNESP]; Cortes, J. A. [UNESP]; Rocha, L. S.R. [UNESP]; Silva, C. C. [UNESP]; Simões, A. Z. [UNESP] (Springer Nature, 2016)
Thin films of BiFeO3 (BFO), LaFeO3 (LFO), and LFO/BFO heterostructures were successfully obtained on Pt/TiO2/SiO2/Si(100) substrates by chemical solution deposition. The films were characterized by structural, morphological and magneto-electrical techniques. The polycrystalline films obtained with good crystalline phases of BFO and LFO. The heterostructures films LFO/BFO showed no diffusion between the phases, and without the presence of secondary phases. The bottom layer of LFO was able to promote the grain growth, reducing oxygen vacancies, and influenced the tension between the new interfaces of the subsequent layer of BFO, thereby altering the physical and chemical properties obtained in the heterostructure. These show the coexistence of ferroelectricity and magnetism in the material. Measurements of capacitance and electrical polarization as a function of the magnetic field have been made and have indicated the magnetic–electric coupling at room temperature with high dielectric constant. Such materials may be of great significance in basic as well as applied research.